Students’ Perception of Using Online Platforms for Listening - Deasy Yunita Siregar; Nazwa Madina Rangkuti; Ahmad Daffa Bangun; Tasya Khalishah Salsabila; Lathifatunnisa Br Situmorang; Humayro Malano (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study examines students’ perceptions of the use of online platforms for English listening practice. The research employs a mixed-methods approach involving 150 undergraduate students through questionnaires and semi-structured interviews. The findings indicate that the majority of students hold positive attitudes toward the use of online platforms, primarily due to time flexibility, diverse content, and the ability to learn independently. Nevertheless, several challenges were identified, including internet connectivity issues that disrupt the learning experience, a lack of personalized feedback, and difficulties in maintaining learning motivation. Features such as adjustable playback speed, the availability of transcripts, and interactive exercises received high levels of satisfaction. Overall, the study concludes that although online platforms have great potential to enhance English listening skills, their effectiveness largely depends on proper implementation, adequate technical infrastructure, and active support from educators. Therefore, this study recommends improvements in technical aspects and the development of more effective learning methods to achieve more optimal outcomes.